2019
DOI: 10.1038/s41598-019-44693-3
|View full text |Cite
|
Sign up to set email alerts
|

Hair Cortisol Measurement by an Automated Method

Abstract: We present the development of the first procedure for hair cortisol measurement through an automated method. Hair samples were obtained from 286 individuals. After cortisol extraction, samples were measured in a Siemens Immulite 2000 (Gwynedd, UK) automated chemoluminiscent immunoassay analyzer. Normal reference values were obtained from hair cortisol levels measured in 213 healthy individuals with low levels of stress. Hair cortisol concentration median was 55 pg/mg hair (2.5–97.5 percentile (40–128)) in heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 24 publications
0
39
1
Order By: Relevance
“…The concentration values obtained in this study were low in comparison with modern dentine data (Nejad et al, 2016), archaeological hair concentrations (Webb et al, 2015a), and modern standards from hair, saliva, blood, and urine (Aardal & Holm, 1995;Deutschbein et al, 2011;Gonzalez et al, 2019). Not all of the samples in this analysis met the minimum detection threshold of the ELISA cortisol kits.…”
Section: Low Concentrations Detectedcontrasting
confidence: 73%
“…The concentration values obtained in this study were low in comparison with modern dentine data (Nejad et al, 2016), archaeological hair concentrations (Webb et al, 2015a), and modern standards from hair, saliva, blood, and urine (Aardal & Holm, 1995;Deutschbein et al, 2011;Gonzalez et al, 2019). Not all of the samples in this analysis met the minimum detection threshold of the ELISA cortisol kits.…”
Section: Low Concentrations Detectedcontrasting
confidence: 73%
“…Third, the majority of participants (70%) have had some hair treatment, and the differences in frequency of hair washing between participants were not measured. At this point, the importance of these factors is not clear, as the majority of studies have found null effects or only small effects regarding hair treatment and/or hair washing ( Gonzalez et al, 2019 , Stalder et al, 2017 ). Other limitations include the use of self-administered questionnaires, the data from which could be biased.…”
Section: Discussionmentioning
confidence: 99%
“…One reference range reported for cortisol in hair is 17.7–153.2 pg/mg of hair (median 46.1 pg/mg) [ 63 ]. A more recent study [ 64 ] reported a hair cortisol concentration reference interval in healthy individuals with low levels of stress to be 40–128 pg/mg of hair while the range for concentrations in stressed individuals was higher (182–520 pg/mg of hair). Hair specimens in our sample were obtained from 44 respondents, mostly because respondents did not have enough hair to provide a sample.…”
Section: Methodsmentioning
confidence: 99%